A SVoD Platforms: A Comprehensive Analysis through Technology Adoption Models - Müller-Pérez, Jessica; Acevedo-Duque, Ángel; Alvarez-Becerra, Rina; Verges, Irma Yomaira (Revista Venezolana de Gerencia, 2025)
Nowadays, companies operating in the Over-The-Top (OTT) market, particularly those within the Subscription Video on Demand (SVoD) model, face increasing diversification and competitiveness with numerous alternatives. Unforeseen developments have necessitated adjustments in the pricing strategy of these platforms. Therefore, the objective of this research is to identify the primary factors affecting the intention of continued use of SVoD platforms through the technology acceptance model (TAM), the Value-based Adoption Model (VAM), and the extended Unified Theory of Acceptance and Use of Technology Model (UTAUT), incorporating new variables. An online survey was conducted with 385 OTT users, and PLS-SEM was employed to measure the model. The results revealed that the variable most influencing the intention of continued use was the perceived value of the viewers, followed by personalization and habit. This study represents one of the initial investigations conducted in Mexico on SVoD platforms, providing valuable insights for SVoD platform administrators to understand the key features they should focus on when adjusting or making strategic changes. This knowledge aims to ensure customer satisfaction and prolonged retention. Additionally, it contributes academically by proposing a new model based on the TAM and VAM frameworks.